OPTIMALISASI PENDAMPINGAN ORANG TUA DALAM MENDIDIK BERBASIS KETELADANAN DAN KASIH SAYANG DI PAUD SKB AL ARAFAH KEDIRI - Wuni Arum Sekar Sari; Novida Aprilina Nisa Fitri (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
This community service program focuses on strengthening education based on affection and exemplary behavior at PAUD SKB Al Arafah, which serves children from families with complex backgrounds, such as divorce, migration, or bereavement. The issues addressed include challenges in parenting styles and the need for a learning environment that supports children's social-emotional development. The goal of this program is to improve the skills of teachers, parents, and guardians in holistically supporting children’s growth and development. The program employs a Participatory Action Research (PAR) approach, involving teachers, parents, and guardians in designing, implementing, and evaluating the program. Activities include teacher training, parenting support, and collaborative activities with children. The results show improvements in children’s social-emotional skills, a transformation in parenting practices to be more responsive, and the strengthening of teachers’ roles as educational facilitators. This educational model has shown positive impacts and can serve as a reference for other institutions.